Statement of Peer Review - Margherita Ferrante; Gea Oliveri Conti (Medical Sciences Forum)
In submitting conference proceedings to Medical Sciences Forum, the volume editors of the proceedings certify to the publisher that all papers published in this volume have been subjected to peer review administered by the volume editors [...]